A protein phosphatase 2C, AP2C1, interacts with and negatively regulates the function of CIPK9 under potassium-deficient conditions in Arabidopsis. (15th May 2018) - Singh, Amarjeet; Yadav, Akhilesh K; Kaur, Kanwaljeet; Sanyal, Sibaji K; Jha, Saroj K; Fernandes, Joel L; Sharma, Pankhuri; Tokas, Indu; Pandey, Amita; Luan, Sheng; Pandey, Girdhar K
Abstract : AP2C1 dephosphorylates CIPK9 to negatively regulate its function in controlling root growth and seedling development under low-K + conditions in Arabidopsis. Abstract: Potassium (K + ) is a major macronutrient required for plant growth. An adaptive mechanism to low-K + conditions involves activation of the Ca 2+ signaling network that consists of calcineurin B-like proteins (CBLs) and CBL-interacting kinases (CIPKs). The CBL-interacting protein kinase 9 (CIPK9) has previously been implicated in low-K + responses in Arabidopsis thaliana . Here, we report a protein phosphatase 2C (PP2C), AP2C1, that interacts with CIPK9. Fluorescence resonance energy transfer (FRET), bimolecular fluorescence complementation (BiFC), and co-localization analyses revealed that CIPK9 and AP2C1 interact in the cytoplasm. AP2C1 dephosphorylates the auto-phosphorylated form of CIPK9 in vitro, presenting a regulatory mechanism for CIPK9 function. Furthermore, genetic and molecular analyses revealed that ap2c1 null mutants ( ap2c1-1 and ap2c1-2 ) are tolerant to low-K + conditions, retain higher K + content, and show higher expression of K + -deficiency related genes contrary to cipk9 mutants ( cipk9-1 and cipk9-2 ). In contrast, transgenic plants overexpressing AP2C1 were sensitive to low-K + conditions. Thus, this study shows that AP2C1 and CIPK9 interact to regulate K + -deficiency responses in Arabidopsis. CIPK9 functions as positive regulator whereas AP2C1 acts as a negative regulator of Arabidopsis root growth and seedling development under low-K + conditions.